Equines as reservoirs of human fascioliasis: transmission capacity, epidemiology and pathogenicity in Fasciola hepatica-infected mules. (10th September 2020) - Mera y Sierra, R.; Neira, G.; Bargues, M.D.; Cuervo, P.F.; Artigas, P.; Logarzo, L.; Cortiñas, G.; Ibaceta, D.E.J.; Lopez Garrido, A.; Bisutti, E.; Mas-Coma, S.
Abstract: Fascioliasis is a zoonotic disease caused by liver flukes transmitted by freshwater lymnaeid snails. Donkey and horse reservoir roles have been highlighted in human endemic areas. Liver fluke infection in mules has received very limited research. Their role in disease transmission, epidemiological importance and Fasciola hepatica pathogenicity are studied for the first time. Prevalence was 39.5% in 81 mules from Aconcagua, and 24.4% in 127 from Uspallata, in high-altitude areas of Mendoza province, Argentina. A mean amount of 101, 242 eggs/mule/day is estimated. Lymnaeids from Uspallata proved to belong to ribosomal DNA internal transcribed spacer (ITS) markers ITS-1 and ITS-2 combined haplotype 3C of Galba truncatula . These lymnaeids were experimentally susceptible to infection by egg miracidia from mules. Infectivity, number of cercariae/snail and shedding period fit the enhanced F. hepatica / G. truncatula transmission pattern at very high altitude. This indicates that the mule is able to maintain the F. hepatica cycle independently. Individual burdens of 20 and 97 flukes were found. Mule infection susceptibility is intermediate between donkey and horse, although closer to the latter. Anatomo-pathology and histopathology indicate that massive infection may cause mule death. Haematological value decreases of red blood cells, haemoglobin, leucocytes and lymphocytes indicate anaemia and strong immunosuppression. Strongly increased biochemical marker values indicate liver function alterations. The mule probably played a role in the past exchanges with Chile and Bolivia through Mendoza province. Evidence suggests that mules could contribute to the spread of both F. hepatica and G. truncatula to human fascioliasis-endemic areas in these countries.